Training needs for special education teachers in special education centers and inclusive schools A field study in the city of Latakia - حيدر, ربا; شعبان, هنادي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research sought to know the training needs of special education teachers in the city of Latakia, and to identify the difference in these training needs according to the variables: workplace, type of disability, number of years of experience, and academic specialization. In order to achieve the goal of the research, the two researchers designed a questionnaire for the training needs of teachers, and applied it to A randomly drawn sample of (56) male and female teachers. The results of the research showed the presence of training needs among the sample members to a moderate degree, as the dimension of rehabilitation and treatment ranked first, followed by behavior modification, then evaluation and diagnosis, and theoretical knowledge came in the last rank. And academically, the results showed that there were statistically significant differences according to the variable number of years of experience in favor of teachers who had more than five years of experience, meaning that they had the highest training need. While the results showed that there were no statistically significant differences between special education teachers according to the rest of the variables.